1996
DOI: 10.1093/comjnl/39.2.124
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Algorithm to Compute the Candidate Keys of a Relational Database Schema

Abstract: We provide an efficient algorithm for computing the candidate keys of a relational database schema. The algorithm exploits the 'arrangement' of attributes in the functional dependencies to determine which attributes are essential and useful for determining the keys and which attributes should not be considered. A more generalized algorithm using attribute graphs is then provided which allows a uniform and simplified solution to find all possible keys of a relational database schema when the attribute graph of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 4 publications
(7 reference statements)
0
19
0
Order By: Relevance
“…Moreover, the discovery of FDs [15,16,19] is also very similar to the problem of discovering uniques, as uniques functionally determine all other individual columns within a table. Thus, some approaches for unique discovery incorporate the knowledge on existing FDs [1,24]. Saiedian and Spencer presented an FD-based technique that supports unique discovery by identifying columns that are definitely part of all uniques and columns that are never part of any unique [24].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the discovery of FDs [15,16,19] is also very similar to the problem of discovering uniques, as uniques functionally determine all other individual columns within a table. Thus, some approaches for unique discovery incorporate the knowledge on existing FDs [1,24]. Saiedian and Spencer presented an FD-based technique that supports unique discovery by identifying columns that are definitely part of all uniques and columns that are never part of any unique [24].…”
Section: Related Workmentioning
confidence: 99%
“…Thus, some approaches for unique discovery incorporate the knowledge on existing FDs [1,24]. Saiedian and Spencer presented an FD-based technique that supports unique discovery by identifying columns that are definitely part of all uniques and columns that are never part of any unique [24]. They showed that given a minimal set of FDs, any column that appears only on the left side of a FD must be part of all keys.…”
Section: Related Workmentioning
confidence: 99%
“…Discovered uniques are good candidates for primary keys of a table. Therefore some literature refers to them as "candidate keys" [8]. The * A full version of this paper is available at [1] Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Unique Column Combinationsmentioning
confidence: 99%
“…Saeidian and Spencer present an FD-based approach that supports unique discovery [8]. They showed that given a minimal set of FDs , any column that appears only on the left side of the given FDs must be part of all keys and columns that appear only on the right side of the FDs cannot be part of any key.…”
Section: Related Workmentioning
confidence: 99%
“…Relative covers have been used previously by Saiedian and Spencer in [17] under the name contraction. We will be using them in the context of implication dependencies, which are functional dependencies over an attribute set of functional dependencies, describing implication between them (see Section 3.4).…”
Section: Relative Coversmentioning
confidence: 99%